Traffic Characteristics on Soekarno Hatta Road After the Operation of Kopo Flyover, Bandung City - Akbardin, Juang; Kurnia Mulyawanti, Widia; Mohamad Ma’soem, Dadang (ASTONJADRO, 2024)
Bandung is one of the major cities in Indonesia located in West Java Province. One of the roads that is often traveled by vehicles in Bandung is Soekarno Hatta road, which is the longest road in Bandung that cuts from Cibiru to Sudirman road. The emergence of congestion on the Soekarno Hatta road in Bandung City is a problem that is often faced by motorists. This is caused by excessive mobility and declining road facilities. The purpose of this study is to analyze the characteristics of traffic flow on Soekarno Hatta Road after the operation of Kopo Flyover, precisely above and below Kopo Flyover, Bandung City. From the results of data analysis, it can be seen that the largest vehicle volume occurred at Point III on Thursday which amounted to 10954.40 skr/hour, the largest speed occurred at Point I on Sunday at 59.10 km/hour and the densest density occurred at Point III on Tuesday at 306.69 skr/km. Traffic performance in terms of degree of saturation (D), at Point I obtained 0.90926 has level of service E, at Point II obtained 0.71992 has level of service C and at Point III obtained 0.93963 has level of service E.